DRUG PRESCRIPTION PROFILE AND PERINATAL DETERMINANTS DURING THE FIRST YEAR OF LIFE. Issue 1 (14th December 2015) - Piovani, Daniele; Clavenna, Antonio; Pavoni, Chiara; Bonati, Maurizio
Abstract : The aim of the study was to investigate the drug prescription profile during the first year of life in a cohort of newborns, and the influence of perinatal and socio-demographic factors on drug prescription. A total of 61, 479 neonates born in 2011 were included. The data source was the database of reimbursed prescriptions of the Lombardy region, Italy. Drug prescriptions were classified according to the Anatomical Therapeutic Chemical (ATC) classification system. Drug prevalence was calculated as the percentage of neonates receiving at least one drug prescription in one year. Chi-square test was used to compare prevalence of drug prescription in males and females. In all, 42, 204 infants (68.7%) received at least one drug prescription, with a prevalence slightly higher in males than females (71.1% versus 66.1%; χ2=178 p<0.01). The drug classes most commonly prescribed in the first year of life were antibiotics (39.5% of infants), anti-asthmatics (32.6%), and corticosteroids for systemic use (9.8%). The median age of first prescription was 20.6 (Interquartile range: 9.4–33.3) weeks. Males received the first prescription about one week before females (20.1 versus 21.3, respectively). The first prescription concerned mainly anti-asthmatics (40.5%), and antibiotics (37.9%), and amoxicillin (16.3%), beclomethasone (16.0%), and amoxicillin+clavulanic acid (15.0%) were the most prescribed drugs. In conclusion, in the first year of life, 7 out of 10 infants received drug prescriptions. Males were more exposed than females, a finding consistent with the epidemiology of diseases in infancy. The analysis concerning the influence of maternal and perinatal factors is ongoing.